Life cycle, morphometry and natural enemies of fall armyworm, spodoptera frugiperda (J.E. Smith) (lepidoptera Noctuidae) on zea mays l. in the Philippines - Navasero, Marcela M. (Journal of ISSAAS, 2020)
The recent introduction of fall armyworm, Spodoptera frugiperda (J.E. Smith) into the country which was first detected in the Cagayan Valley, the major corn growing area, has the potential to cause yield losses, in the absence of effective control measures. This paper sought to describe briefly the development stages of S. frugiperda and determine its life history parameters on a locally bred variety of corn (var. Lagkitan), as a new food source, being a newly introduced pest. It also determined the morphometrics of the different life stages; larval damage, pupation and behavior, including its natural enemies collected from the field in several provinces in the Philippines. A short development time and high reproductive rate of the pest was demonstrated when fed with young leaves of corn under laboratory conditions.